Development of Guided Inquiry based E-Learning Teaching Material on the Intermolecular Forces Enriched with Molview - Nur Indah Agustina; Munzil Munzil; Habiddin Habiddin; M. Muchson (Journal of Disruptive Learning Innovation (JODLI), 2021)
The intermolecular force is one of the chemistry topics covered in the high school curriculum in Indonesia. As the characteristics of chemistry concepts in general, intermolecular forces concepts can be presented in the three levels of chemical representations (microscopic, symbolic, and macroscopic).  Currently, chemistry teaching materials are available in Indonesian schools mostly have limited support for helping students to visualize the molecular aspect of intermolecular forces concepts mainly in the form of three-dimensional space (3D). This study aimed to produce an E-Learning teaching material enriched with 3D Molecular Visualization. The product (teaching material) in this study is presented by considering the syntax of guided inquiry-based learning. The product was developed with the procedure adopted from Lee and Owens, including assessment/analysis, need assessment, front-end analysis, design, and development. The product is valid and suitable to be applied in online chemistry teaching. However, further study to investigate the effectiveness of this product empirically need to be explored in the future.